2000
DOI: 10.1046/j.1365-2133.2000.03425.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioid cell lymphoma (Lennert’s lymphoma) presenting as atypical granuloma annulare

Abstract: We describe a case presenting as atypical granuloma annulare where the underlying diagnosis, confirmed by lymph node biopsy, was lymphoepithelioid cell lymphoma (Lennert's lymphoma). Lennert's lymphoma is a peripheral T-cell lymphoma which may follow a variable course and transform into an aggressive phase. Cutaneous manifestations of this condition have only rarely been reported in the literature. The presence of granulomas in the skin may have either obscured the lymphoma infiltrate or may have reflected a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…Prominent clusters of epithelioid histiocytes were consistent with diagnostic criteria for lymphoepithelioid lymphoma [1]. Previous anecdotal reports have shown a granuloma annulare-like skin lesion, prurigo nodularis or non-specific reactive dermatosis without cellular atypia as cutaneous manifestations of LL [1,3,4]. A careful retrospective review of the skin lesions also confirmed the involvement of lymphoma within the skin ( figure 1E).…”
Section: Chronic Granulomatous Dermatosis As a Presenting Sign Of A Lsupporting
confidence: 78%
“…Prominent clusters of epithelioid histiocytes were consistent with diagnostic criteria for lymphoepithelioid lymphoma [1]. Previous anecdotal reports have shown a granuloma annulare-like skin lesion, prurigo nodularis or non-specific reactive dermatosis without cellular atypia as cutaneous manifestations of LL [1,3,4]. A careful retrospective review of the skin lesions also confirmed the involvement of lymphoma within the skin ( figure 1E).…”
Section: Chronic Granulomatous Dermatosis As a Presenting Sign Of A Lsupporting
confidence: 78%
“…Skin granulomas are considered as a peculiar immunological hypersensitivity reaction of the host against the tumor cells or persisting viral antigens such as HTLV-1. 13,16 An alternative explanation could be the persistence of unidentified opportunistic infectious agents. Support for this hypothesis may derive from the finding in a patient of acid-fast coccoid forms in both lymphoma and cutaneous sarcoid lesions.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 GA and clinically atypical GA have been reported in patients with lymphomas. [6][7][8][9] Clinically atypical GA and necrobiosis lipoidica have also been associated with systemic diseases. 10 The pathogenesis of GA is uncertain.…”
mentioning
confidence: 98%